Comparison of KRAS Mutation Assessment in Tumor DNA and Circulating Free DNA in Plasma and Serum Samples - Shethah R. Morgan; Jessica Whiteley; Emma Donald; John Smith; Marcia T. Eisenberg; Eddie Kallam; Lauren Kam-Morgan (Clinical Medicine Insights: Pathology, 2012)
Testing for mutations in the KRAS oncogene for patients with metastatic colorectal cancer (mCRC) is generally performed using DNA from formalin-fixed paraffin-embedded tumor tissue; however, access to specimens can be limited and analysis challenging. This study assessed the identification of KRAS mutations in circulating free DNA (cfDNA) using a commercially available KRAS polymerase chain reaction (PCR) kit. Matched plasma, serum and tumor samples were available from 71 patients with mCRC who had received prior therapy but whose disease progressed following therapy. Yields of cfDNA from plasma and serum samples were comparable. Analyses were successful in 70/71 plasma-extracted samples (specificity: 97%, sensitivity: 31%) and 67/71 serum-extracted samples (specificity: 100%, sensitivity: 25%). This study demonstrates that KRAS mutations can be detected in cfDNA using a commercially available KRAS PCR kit, confirming cfDNA as a potential alternative source of tumor DNA in a diagnostic setting if access to archival tumor specimens is limited.